Microbial substrate stoichiometry governs nutrient effects on nitrogen cycling in grassland soils. (April 2021) - Schleuss, P.M.; Widdig, M.; Biederman, L.A.; Borer, E.T.; Crawley, M.J.; Kirkman, K.P.; Seabloom, E.W.; Wragg, P.D.; Spohn, M.
Abstract: Human activities have increased nitrogen (N) and phosphorus (P) inputs in terrestrial ecosystems and altered carbon (C) availability, shifting the stoichiometry of microbial substrates in soils, such as the C:N:P ratios of the dissolved organic matter pool. These stoichiometric deviations between microbial biomass and its substrate may control microbial processes of N cycling. We studied the effects of this stoichiometric mismatch using a full factorial N and P addition experiment replicated in six grassland ecosystems in South Africa, the USA, and the UK. We found that N and P addition changed the dissolved organic matter C:N ratio, but not the C:N ratio of the soil microbial biomass. Compared to P addition, N addition decreased microbial N acquisition via non-symbiotic N2 fixation by −55% and increased microbial N release via net N mineralization by +134%. A possible explanation is that the dissolved elements, e.g., dissolved organic C (DOC) and dissolved total N (DN), serve as the main microbial substrate and its C:N ratio defines whether N is scarce or abundant with respect to microbial demands. If N is available in excess relative to microbial demands, net N mineralization increases. In contrast, when N is scarce, immobilization outweighs release decreasing net N mineralization. However, the activity of leucine aminopeptidases, which decompose peptides, was not affected by nutrient additions. Further, C rather than P availability may control the rates of non-symbiotic N2 fixation in the six studied grassland sites. In conclusion, globally increasing nutrient inputs change processes of microbial N acquisition and release in grassland ecosystems and these changes are largely driven by shifts in substrate stoichiometry. Graphical abstract: Image 1 Highlights: We investigated N cycling processes upon N and P addition in six grassland soils. N and P addition had no significant effect of microbial biomass stoichiometry. N cycling processes were largely driven by changes in substrate stoichiometry. N addition decreased microbial N2 fixation and increased net N mineralization. N and P addition did not affect the activity of leucine-aminopeptidases.